The Effectiveness of Android-based Thermodynamics Digital Book Integrated with PhET Simulations to Improve Students’ Graphical Representation Skills - Tantri, Risma; Supahar, Supahar; Jumadi, Jumadi; Kurniawan, Lilik (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
A digital book is one of the media that can support learning because has the easiest access and can be equipped with multimedia features such as simulations. This research aims to determine the effectiveness of an Android-based thermodynamics digital book integrated with PhET simulation to improve students' graphical representation skills. The independent variable in this research is an Android-based thermodynamics digital book integrated with PhET simulations. In contrast, the dependent variable in this research is the ability of graphical representation skills. This research type is pre-experimental using a one-group pretest-posttest research design. At State High School in Yogyakarta, 72 students in the 11th grade participated in the cluster random sampling technique. N-Gain and eta square values showed that the students' graphical representation skills were significantly enhanced by the android-based thermodynamics digital book integrated with PhET simulation. This points out that using electronic physics learning materials and integrating technology has a positive effect on improving graphical representation skills. The recommendations made based on this research include that observation sheets be added to future research to observe the students better as they engage in each learning activity.